Analisis Pengaruh Karakteristik Wirausaha dan Strategi Pemasaran Terhadap Keberhasilan UMKM di Bidang Makanan dan Minuman di Kecamatan Koba pada Era Digital - Natalia Natalia; Medinal Medinal; Fery Panjaitan; Rizal R. Manullang (Transformasi Manageria: Journal of Islamic Education Management, 2024)
This study aims to determine how much influence entrepreneurial characteristics and marketing strategies have on the success of MSMEs in the food and beverage sector in Koba District in the Digital Era. The sample of this study consisted of 82 respondents, determined using the Slovin formula and the sampling technique used was purposive sampling. The data collection technique was carried out using a questionnaire. The results of this study indicate that (1) Entrepreneurial characteristics have a partial positive effect on the success of MSMEs with a significance value of 0.001 <0.05 and a t-count value of 7.559> t-table 1.990. (2) Marketing Strategy has a partial positive effect on the success of MSMEs with a significance value of 0.001 <0.05 and a t-count value of 3.467> t-table 1.990. (3) Entrepreneurial Characteristics and Marketing Strategy have a simultaneous positive effect on the success of MSMEs with a significance value of 0.001 <0.05 and an F-count value of 49.937> F-table 3.112.